TATA KELOLA ASET TETAP TANAH DAN BANGUNAN DI DINAS KESEHATAN KABUPATEN TANAH BUMBU - Nurul Susilawati; Iswiyati Rahayu; Singgih Priono (STIA Bina Banua Banjarmasin, 2019)
This study aims to: 1) To know the governance of fixed assets in the form of land and buildings in the District Health Office Tanah Bumbu, 2) To know the constraints in the governance of fixed assets in the form of land and buildings in the District Health Office Tanah Bumbu. 3) To find alternative solutions needed to overcome obstacles in the governance of fixed assets in the form of land and buildings in the District Health Office Tanah Bumbu. This research is a qualitative descriptive study. Informants in the study are employees in charge of managing assets in the District Health Office Tanah Bumbu. Data were collected through structured interviews, observation and documentation. The results of the research indicate that: 1) Governance of fixed assets in the form of land and buildings within the District Health Office of Tanah Bumbu has been implemented well because every stage of governance consisting of planning, organizing, implementation up to supervision has been implemented based on governance principles good, namely: Transparent, accountable, responsibel, independent and fair, 2) Constraints in governance of fixed assets District Health Office Tanah Bumbu, namely: a. The existence of an Asset that is borrowed but is recognized as a village asset, and b. The existence of Non-Conformity between Listing in KIB with reality, 3) Alternative solution to overcome obstacle in governance of fixed asset of District Health Office of Tanah Bumbu namely: a. The existence of Assets Hundred Treated but Recognized as a Village Asset can be overcome with the delivery of fixed assets to the Village through Grants, and b. The existence of Non-Conformity between Registration in KIB with reality can be overcome through reconciliation held periodically that is 3 (three) months. 1) Untuk mengetahui tata kelola aset tetap berupa tanah dan bangunan di Dinas Kesehatan Kabupaten Tanah Bumbu, 2) Untuk mengetahui kendala dalam tata kelola aset tetap berupa tanah dan bangunan di Dinas Kesehatan Kabupaten Tanah Bumbu. 3) Untuk mencari alternatif solusi yang diperlukan guna mengatasi kendala dalam tata kelola aset tetap berupa tanah dan bangunan di Dinas Kesehatan Kabupaten Tanah Bumbu. Penelitian ini merupakan penelitian deskriptif kualitatif. Informan dalam penelitian adalah pegawai yang bertugas mengelola aset di Dinas Kesehatan Kabupaten Tanah Bumbu. Data dikumpulkan melalui wawancara terstruktur, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa: 1) Tata kelola Aset tetap berupa tanah dan bangunan di lingkungan Dinas Kesehatan Kabupaten Tanah Bumbu telah terlaksana dengan baik karena setiap tahapan tata kelola yang terdiri dari perencanaan, pengorganisasian, pelaksanaan sampai dengan pengawasan sudah dilaksanakan dengan berdasarkan pada prinsip tata kelola yang baik, yaitu : Transparan, akuntabel, responsibel, independen serta wajar, 2) Kendala dalam tata kelola aset tetap Dinas Kesehatan Kabupaten Tanah Bumbu, yaitu : a. Adanya Aset Yang Berstatus Pinjam Pakai Namun Diakui Pula sebagai Aset Desa, dan b. Adanya Ketidaksesuaian antara Pencatatan di KIB dengan kenyataan, 3) Alternatif solusi guna mengatasi kendala dalam tata kelola aset tetap Dinas Kesehatan Kabupaten Tanah Bumbu yaitu : a. Adanya Aset Yang Berstatus Pinjam Pakai Namun Diakui Pula sebagai Aset Desa dapat diatasi dengan Penyerahan aset tetap kepada Desa melalui Hibah, dan b. Adanya Ketidaksesuaian antara Pencatatan di KIB dengan kenyataan dapat diatasi mealui rekonsiliasi yang diadakan secara berkala yaitu 3 (tiga) bulan sekali